CONNECTIVIST LEARNING IN THE SOUTH AFRICAN TECHNOLOGY RICH SCHOOLS - Dineo Shirindi, Charlotte (2025)
The South African education policy, the Curriculum Assessment Policy Statement (CAPS) envisions the utilisation of ICTs for teaching and learning in all subjects and yet, it is silent on the pedagogical approaches to be employed by teachers, to achieve their learning outcomes using ICTs. In this multiple case study, focus was on four Grade 8 Technology teachers teaching in technology rich (Full ICT) schools in one of the provinces, Gauteng. It sought to understand how they created opportunities for learners to acquire the desired network society skills, to solve real-life or authentic problems and thus prepare them for meaningful participation in the global world. The Guided Blended Connectivist Learning (GBCL) Framework was developed and used to analyse data from teacher interviews, lesson observations, lesson plans and social media. Coding (thematic analysis) was used to analyse data. The literature reviewed reveals constraining factors inherent in the utilisation of ICTs in the South African context, which negatively impact the development of Learner Network Society Skills (LNSS). These include lack of access to connectivity, classroom management skills in the context of ICTs, lack of ICT devices by most learners, inadequate ICT teacher training and support. However, the findings reveal that the Technology teachers in the participating schools shied away from a mechanistic application of existing models and customised teaching and learning approaches to suit their context. Accordingly, teacher professional development programmes should be guided by research findings such as this, to design and equip teachers with appropriate ICT pedagogical skills for the benefit of the achievement of curriculum goals, in the context of utilising ICTs.